2015
DOI: 10.2514/1.t4482
|View full text |Cite
|
Sign up to set email alerts
|

Moving-Boundary Model of Cryogenic Fuel Loading, II: Theory Versus Experiments

Abstract: A moving-boundary model of two-phase cryogenic flow, which was developed in the companion paper (Hafiychuk, V., Foygel, M., Ponizovskaya-Devine, E., Smelyanskiy, V., Watson, M., Brown, B., and Goodrich, C., "Moving-Boundary Model of Cryogenic Fuel Loading, I: Two-Phase Flow in a Long Pipe," Journal of Thermophysics and Heat Transfer (to be published)), is applied toward simulation of liquid nitrogen flow data collected for the cooldown regime in two different experimental fuel transfer lines: 1) the 1966 Natio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…An extensive numerical testing revealed that this can be done e.g. by adding to the hierarchy homogeneous moving-boundary quasi-steady model of two-phase cryogenic flow [16,17] as will be discussed below.…”
Section: Separated Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…An extensive numerical testing revealed that this can be done e.g. by adding to the hierarchy homogeneous moving-boundary quasi-steady model of two-phase cryogenic flow [16,17] as will be discussed below.…”
Section: Separated Modelmentioning
confidence: 99%
“…To speed up integration of the model [16,17] the momentum equation is solved in the quasisteady approximation, neglecting inertia terms ( () ,z denote spatial derivative)…”
Section: Homogeneous Moving Front Modelmentioning
confidence: 99%
See 3 more Smart Citations